The new constitution of the Scott Polar Research Institute (Polar Record, 1957)
In the last issue of the Polar Record an impending readjustment of the constitution of the Scott Polar Research Institute was announced. This was formally approved by the University on 23 February 1957, and comes into force as from 1 January 1957. The following is the full text of the report of the General Board of the University: The General Board beg leave to report to the University as follows: 1. The principle of the establishment of a Scott Polar Research Institute and the provision of temporary accommodation for it in the Sedgwick Museum of Geology were approved by Grace 4 of 26 November 1920 on recommendations contained in a Report, dated 11 November 1920, of the Council of the Senate on the proposed establishment and endowment of an institute for polar research as a memorial to Captain Scott. The essential features of the institute which the Council recommended for establishment were stated in the preamble of the Council's Report as including: 1. A comprehensive collection of all polar literature into a library.